SIGNIFIER OF BRAND NAME RELATED TO BRAND IMAGE FOR MUSLIM CONSUMER - Harun, Mohd Fauzi; Vincent Amos@Mohd Fadly , Fareez; Al Bakry , Nur Safinas; Hanafi , Hafizul Fahri; Abd Rahman, Khairol Ezedy (Online Journal of Islamic Management and Finance (OJIMF), 2025)
Brand name is one of the bases in elaborative information processing in driving a positive consumer attitude by the cultural attribute, but the manipulation of consumer self-preferences can be deceiving and wrongly interpreted; especially to Muslim consumers in different societal backgrounds of Malaysia. Therefore, the purpose of this study is to explore brand names as a cultural value in Muslim consumer preferences, and to discuss the impacts of brand names to brand image. Qualitative study by interviewing six informants from maximum variation sampling were selected for this study; ranging from designers/art directors, academicians, and marketers. Thematic analysis was used to transcribe the dataset with the discovery of four main themes: target audience, emphasis, attention, and trust. The findings suggest that cultural values in brand names are complex but the usage is significant to be applied by all to represent the local marketplace and attention of the target audience. Brand name alone cannot be representative of brand image, but it has a distinctive impact on recognition. Culture has a great influence towards branding stimuli of Muslim consumers beyond the limits of the exchange of goods. Hopefully, this study will inform practitioners regarding options to reduce the noise of brand communication efficacy for the application of brand name. In addition, consumer side of view regarding the topic can be explore more to gain deeper insights into their expectations and preferences related to brand image.